Ryff Scale of Well-Being: Factorial Structure of Theoretical Models in Different Age Groups [Escala de Bienestar de Ryff: Análisis Comparativo de Los Modelos Teóricos en Distintos Grupos de Edad] - Vera-Villarroel, P; Pavez-Salinas, P; Celis-Atenas, K (2013)
The scale of psychological well-being arises from the multidimensional model proposed by Ryff (1989). Despite its wide use, its initial theoretical structure has not been completely confirmed because other factorial solutions which are different from those 6 dimensions proposed by the author have been found. These differences may be related to the type of sample and population used. Given this fact, the current study compares the adjustment factor of correction models traditionally used in different groups of adults. We describe the psychometric properties of the Spanish adaptation done by Díaz et al. (2006) and analyze the levels of reliability (internal consistency and temporal stability) and confirmatory factorial structure with data from 1,646 people aged from 18 to 90 years old. Differences are found in the indicators of reliability for the total scale and its dimensions as well as in the indicators of goodness of fit depending on the age group. The model that presents the best indicators of adjustment for most age ranges evaluated was the one of six first-order factors.